CORNELLI, G. O pitagorismo como categoria historiográfica. Classica Digitalia Brasil. CECHUniversidade de Coimbra/ Annablume, Coimbra/São Paulo, 2011. ISBN 978-85-64608-05-4 - Bordoy, Francesc Casadesús (Revista Archai, 2011)
CORNELLI, G. O pitagorismo como categoria historiográfica. Classica Digitalia Brasil. CECHUniversidade de Coimbra/ Annablume, Coimbra/São Paulo, 2011.